Discovery of association rules between factors affecting user satisfaction in software project by FP-GROWTH Algorithm - Kaewbanjong, Katawut; Intakosum, Sarun (My University, 2021)
The main objective of this work was to find the association rules between factors affecting user satisfaction in software project by using an association rule discovery technique. Data from 191 software projects were collected and association rules between 15 Selected factors were discovered by FP-growth algorithm. Primarily, 281 association rules were discovered. Rules that were not directly related to user satisfaction were filtered out by simple criteria. In the end, 11 final association rules that passed those criteria were obtained with an average confidence value of 65.30%. These rules can incorporated in the planning and administration of a software project to gain utmost user satisfaction
Keywords: Association rule; FP-Growth algorithm; Software project; User satisfaction